Objective evaluation of the relationship between facial expression analysis by the facial action coding system (FACS) and CT/MRI analyses of the facial expression muscles. Issue 5 (6th April 2020) - Okuda, Itsuko; Yamakawa, Yumika; Mitani, Nobu; Ota, Naoko; Kawabata, Marie; Yoshioka, Naoki
Abstract: Background: There are few reports on the relationship between facial expression formation and mass of the muscle responsible for facial expression. We analyzed the facial expression using facial action coding system (FACS) and examined the muscle mass and characteristics of the facial expression muscles using multi‐detector row computed tomography (MDCT) and magnetic resonance imaging (MRI). Moreover, the relation between these was statistically evaluated. Materials and Methods: Ten healthy women in their 40s (43.4 ± 3.0 years, 40‐49) were enrolled. The expressive faces were analyzed by facial expression analysis software based on the FACS. The muscle mass and characteristics of the facial expression muscles were investigated using MDCT/MRI. The correlation between an integrated expression intensity value (IEIV) for FACS of the widest possible grin and muscle mass was analyzed. The mean values between the two categorized groups (G‐1 and G‐2) based on fat infiltration into the muscle were compared. Results: A positive correlation is found between the IEIV and the muscle mass. The IEIV of G‐1 is significantly larger than the corresponding value of G‐2. Hence, the results indicated that the subjects with high IEIV and expressive face had thicker facial expression muscles and little fat infiltration into the muscles. Conclusion: Our objective imaging diagnostic study using FACS, MDCT, and MRI corroborated the anti‐aging medical science about the facial expression muscles related to youthful facial appearance. The results of this research could contribute to the elucidation of the mechanisms involved in the facial aging process and to the development of cosmetology.